Nuclear medicine and molecular imaging - O'Malley, Janis P; Ziessman, Harvey A (Elsevier, 2021)
The publication focuses on new molecular imaging methods and their clinical application. Intended for professionals.
The requisites
Keywords: nukleární lékařství; Molecular Imaging; molekulární biologie, molekulární medicína; radiologie; radiologie, nukleární medicína a zobrazovací metody; Radiology; molekulární zobrazování; Nuclear Medicine; klinická studie jako téma; Clinical Studies as Topic